The Absurdity in Waiting for Godot and Endgame by Samuel Beckett: A Comparative Study - Alin Ambarwati; Masduki Zakaria; Islam Ragab Abdelhamid Shehata (MASI Mandiri Edukasi, 2026)
The phenomenon underlying this study is the increasing crisis of meaning and existential uncertainty in modern human life. This condition is reflected in Samuel Beckett’s Waiting for Godot and Endgame, both of which portray characters trapped in cycles of waiting, repetition, and existential emptiness. Although previous studies have examined these plays individually within the Theatre of the Absurd, there is a lack of comparative research that systematically analyzes how absurdity is differently constructed in both works. This study addresses that gap. This research aims to analyze the forms and representations of absurdity through a comparative approach. Using a descriptive-qualitative method, the study applies textual analysis focusing on dialogue, dramatic structure, characterization, and setting. The findings reveal that Waiting for Godot represents absurdity through endless waiting, repetitive dialogue, and unclear identity and purpose. In contrast, Endgame depicts a static, post-apocalyptic environment shaped by dominance, dependency, and the awareness of an inevitable ending. While both plays convey existential meaninglessness, they differ in the intensity of their conflicts, the dynamics of their relationships, and their symbolic representations of space and time. This study contributes by offering a comparative perspective that deepens understanding of absurdity in Beckett’s works and highlights their critique of post–World War II existential conditions.